Methods of Poverty Analysis: the Experience of European Countries - Karpuškienė, Vita (Ekonomika, 1997)
Poverty is a variab1e condition with multiple effects on human life. There is no universal definition of poverty and it is understood differently in different countries. The poverty line is the criterion with which politicians or researchers distinguish whether people or households are poor. There are two main types of poverty lines: the absolute and the relative poverty line. Various methods are used to calculate both types of poverty line. They can be distinguished into the following groups: the budget or consumption basket; the subjective method; the economic distance method; and legal or political methods.